Integrated Eutopic Endometrium and Non‐Depleted Serum Quantitative Proteomic Analysis Identifies Candidate Serological Markers of Endometriosis. Issue 3 (29th November 2018) - Manousopoulou, Antigoni; Hamdan, Mukhri; Fotopoulos, Miltiadis; Garay‐Baquero, Diana J.; Teng, Jie; Garbis, Spiros D.; Cheong, Ying
Abstract : Background: Endometriosis affects about 4% of women in the reproductive age and is associated with subfertility. The aim of the present study is to examine the integrated quantitative proteomic profile of eutopic endometrium and serum from women with endometriosis compared to controls in order to identify candidate disease‐specific serological markers. Methods: Eutopic endometrium and serum from patients with endometriosis ( n = 8 for tissue and n = 4 for serum) are, respectively, compared to endometrium and serum from females without endometriosis ( n = 8 for tissue and n = 4 for serum) using a shotgun quantitative proteomics method. All study participants are at the proliferative phase of their menstrual cycle. Results: At the tissue and serum level, 1214 and 404 proteins are differentially expressed (DEPs) in eutopic endometrium and serum, respectively, of women with endometriosis versus controls. Gene ontology analysis shows that terms related to immune response/inflammation, cell adhesion/migration, and blood coagulation are significantly enriched in the DEPs of eutopic endometrium, as well as serum. Twenty‐one DEPs have the same trend of differential expression in both matrices and can be further examined as potential disease‐ and tissue‐specific serological markers of endometriosis. Conclusions: The present integrated proteomic profiling of eutopic endometrium and serum from women with endometriosis identify promising serological markers that can be further validated in larger cohorts for the minimally invasive diagnosis of endometriosis.